Innowacyjność w okresie kryzysu gospodarczego - Matkowska, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The aim of this article is to review the thesis of the negative impact of the downturn in business on the investment strategies of companies. It covers the issue of innovation during the economic crisis, focusing attention on the problems concerning companies in Poland. The article concludes with the investigation of the relationship between innovation and ensuring the competitiveness of the economy. Innovative activity is not widespread in Polish enterprises. Innovative dynamism is relatively small among them, and the Government has no long-term, developed and coherent strategy to promote innovation through the sharing of information, cooperation with science centers, cheap loans or reduction of taxes. Innovative activity should be permanently inscribed in the activities of companies to make them competitive on the homogenous European market. Nowadays, innovation should be a basic issue in every business, as it is a prerequisite for increasing the attractiveness of the goods and services, which entails the development of the export market and decides on the company’s position in the environment. The most successful companies on the market are those that devote more effort in researching and implementing innovation.
Keywords: innowacyjność; kryzys gospodarczy